Hierarchical mesoporous bio-polymer/silica composites co-templated by trimethyl chitosan and a surfactant for controlled drug delivery - Rana, Vijay Kumar; Park, Sung Soo; Parambadath, Surendran; Kim, Mi Ju; Kim, Sun-Hee; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Medchemcomm, 2011)
In this communication, we report the facile synthesis of hierarchical mesoporous bio-polymer/silica composite materials with bimodal mesopores using a dual-template of the cationic N,N,N-trimethyl chitosan (TMCs) and the anionic sodium dodecyl sulfate (SDS) via one-step synthetic strategy. Tetraethoxysilane (TEOS) was used as a silica source. The nitrogen adsorption/desorption measurements and transmission electron microscopy analysis showed the hierarchical structure of the mesoporous bio-polymer/silica composites with bimodal mesopores having an average pore size of 5-7 nm with the visible voids between the silica nanoparticles, which allow the mesoporous bio-polymer/silica composites to encapsulate a large number of guest drug molecules, Ibuprofen (IBU) or 5-fluorouracil (5-FU), due to their high surface area and pore volume. In addition, the mesoporous chitosan-silica composites also had a long term biocompatibility for the target release of the drug molecules to the CEM cells, MCF cells, etc. as well as a pH sensitive controlled release behavior of the drug molecules.